Equiatomic quaternary (Y1/4Ho1/4Er1/4Yb1/4)2SiO5 silicate: A perspective multifunctional thermal and environmental barrier coating material. (15th July 2019) - Ren, Xiaomin; Tian, Zhilin; Zhang, Jie; Wang, Jingyang
Abstract: Equiatomic quaternary (Y1/4 Ho1/4 Er1/4 Yb1/4 )2 SiO5 solid solution is investigated as a multifunctional thermal and environmental barrier coating (TEBC) material in this work. Dense and pure materials were prepared by hot pressing method, and the compositional homogeneity at macroscale and atomic scale were confirmed by electron-dispersive spectrometer elemental mapping and high-angle annular dark-field images. The quaternary solid solution displays balanced optimal properties on Young's modulus, thermal conductivity, thermal expansion, and high temperature water vapor resistance. The moderate cocktail effects also provide suggestions on the design of rare earth monosilicate TEBC materials. Graphical abstract: Unlabelled Image